Empowering students’ critical thinking skills, information literacy and cognitive learning outcome through RBL-TPS model - Siti S. Narahaubun; Johanis F. Rehena; Dominggus Rumahlatu (University of Muhammadiyah Malang, 2020)
The use of proper learning model by teachers’ in a class room is crucial to be done in addressing the better learning quality. This study aimed at improving learning quality by choosing the most optimum learning model. This research was a quasi-experimental study using nonequivalent pretest-posttest control group design. This study was conducted in Senior High School 9 and Senior High School 5 of Ambon in academic year 2018/2019.The total sample used in this research was 127 students. The Critical Thingking Skills (CTS) and Cognitive Learning Outcome (CLO) tests as well as information literacy observation sheets were used as the instruments to gain the data. The data obtained in terms of students’ CTS, CLO ang information literacy were analyzed using inferential statistics (ANCOVA and LSD tests). The results showed that there were significant differences among X graders’ CTS, CLO, and information literacy [F(1,124) = 64.380, F(1,124) = 68.238 F(1,124) = 26.078 , p < 0.05] respectively, who were taught using RBL-TPS learning model in biodiversity material. In the other words, the RBL-TPS learning model is able to empower students’ CTS, CLO, and information literacy compared to the common learning model used by biology teachers. Thus, the used of RBL-TPS is recommended to be implemented in the other biology learning materials.